2005
DOI: 10.1097/01.mcp.0000162378.35928.37
|View full text |Cite
|
Sign up to set email alerts
|

Pleural effusions in systemic amyloidosis

Abstract: Large pleural effusions in systemic amyloidosis occur most often in primary systemic amyloidosis, predominantly resulting from direct infiltration of the parietal pleural surface. Left atrial hypertension from primary systemic amyloidosis cardiomyopathy contributes to but is not sufficient to form and sustain these effusions. Untreated patients have a median survival of 1.6 months. Secondary, familial, and senile systemic amyloidosis do not infiltrate the pleural surfaces or induce pleural effusions in a clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 29 publications
(12 reference statements)
1
34
0
Order By: Relevance
“…Pleural effusions are an uncommon complication of systemic amyloidosis, most frequently occurring in AL amyloidosis (*6%-18% of cases) [1]. Management of patients with primary systemic amyloidosis and pleural effusions is challenging and once refractory effusions develop, prognosis is poor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pleural effusions are an uncommon complication of systemic amyloidosis, most frequently occurring in AL amyloidosis (*6%-18% of cases) [1]. Management of patients with primary systemic amyloidosis and pleural effusions is challenging and once refractory effusions develop, prognosis is poor.…”
Section: Discussionmentioning
confidence: 99%
“…Management of patients with systemic amyloidosis (AL) who present with diuretic-refractory pleural effusions is challenging and is associated with a poor prognosis [1]. As there are few alternatives for patients who fail conventional treatment, new approaches for pleural effusion management in these patients are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Pleural effusions appear to occur not infrequently in patients with systemic amyloidosis, (17), with the most frequent cause being congestive heart failure. Other explanations include liver failure, nephritic syndrome, and direct pleural deposition with amyloidosis (18).…”
Section: Discussionmentioning
confidence: 99%
“…The English literature, between the years 1977 and 2010, includes 25 case reports of PEs associated with AL, 21 of which document pleural amyloid infiltration [10,41,42,43,44,45,46]. Pleural fluid analysis revealed that 10 out of 17 patients (60%) presented with an exudate, while the rest of the patients (40%), all with congestive heart failure associated with AL, had a transudate.…”
Section: Amyloidosismentioning
confidence: 99%